Value based performance reporting : a study of the information used by Australasian analysts in their assessment of long-term firm performance (value) : a thesis presented in partial fulfillment of the requirements for the degree of Master of Business Studies in Accounting, Massey University - Macfarquhar, Clay Colin (Massey University, 2007)
Public company shareholders and potential investors rely on statutory and voluntary disclosures to enable an informed assessment of company performance and value. It is widely acknowledged that traditional historic accrual accounting measures do not offer a complete picture of firm performance, and that there is demand for an expanded set of performance indicators to service the needs of concerned stakeholders. The reliance on voluntary disclosure of company specific non-financial information is of particular concern to this thesis as the examination of existing literature displays evidence that such areas of performance are under-reported externally. With reference to a range of performance indicators that New Zealand and Australian Chartered Financial Analysts identify as relevant in their assessment of performance and value, this study identifies areas of performance that are under-reported by management and where information asymmetry is proposed to exist. The issue of under-reporting is assessed through gap analysis comparing the surveyed analysts ratings for the 'predictive value' (PV) measure of each performance item/indicator to the respective ratings for 'ease of acquisition' (EA). The study finds that analysts rely on a broad range of financial and non-financial information in their assessment of firm performance. More specifically the reporting of traditional financial information remains relevant and the extent of its provision is adequate, however the study finds that in many cases information not forming part of traditionally reported financial information has 'predictive value' relevance but is relatively more difficult to acquire. The thesis research findings therefore indicate that information reporting reliant on voluntary disclosure is at greater risk of being under-reported (externally). Such under-reporting has been found to be associated with non-financial information that relies on management identifying relevant company specific measures and subsequent voluntary disclosure. In an attempt to emphasise the importance of restoring the information balance between management and interested external parties (for performance assessment and valuation purposes), the thesis will include an exploration and discuss of literature on the benefits associated with full disclosure, along with potential means of identifying relevant measures for external reporting.
Keywords: Financial statements; Disclosure in accounting; Business enterprises -- Valuation